Application of the Unary Codes Algorithm for Compressing Video Files in the Kinemaster Application - Anderson Situmorang, Johanes (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Speed in sending information is something that is really needed in today's technology. Information is a message or a collection of messages or data that has been processed to produce something needed by those in need. Information can take the form of various data formats, including text, video or images. The problem of sending information speed is often a little hampered due to the large file size of the information. In addition, the security factor is also very important, because there are many irresponsible parties who will try to steal this information and can harm the party whose information has been stolen if the information is misused. The data used has a very large size. For that we need a technique to change the size of the data to make it smaller. This technique is called compression or what we are more familiar with as compression. Data compression is a process of converting a set of data into a form of code to save the need for data storage space. In this study, researchers used the Unary Codes algorithm in compressing video files.